Synthesis of Semiconducting Nanoparticles Using Infrared Radiation Assisted Stokes’ Law: A Novel Approach - Shrestha Tyagi; Manohar Singh; Beer Pal Singh (New Approaches in Engineering Research Vol. 10, 2021)
The synthesis of nanomaterials and nanostructures is an important aspect of nanoscience and nanotechnology. New physical properties and applications of nanomaterials are only possible when nanostructured materials are made available with desired size, shape, morphology, crystal structure, and chemical composition. For this reason, in order to explore novel physical properties and phenomena to realize potential applications of nanomaterials, the ability to fabricate and process nanomaterials is the foremost cornerstone in the research and development of nanotechnology. This chapter provides a clear and concise understanding with detailed review work on the synthesis of nanomaterials through a kinetic approach using well-known Stokes’ law for a free body falling in a quiescent and viscous fluid.